2014
DOI: 10.1371/journal.pone.0105674
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage-Specific Ablation of Site-1 Protease in Mice Results in the Endoplasmic Reticulum Entrapment of Type IIB Procollagen and Down-Regulation of Cholesterol and Lipid Homeostasis

Abstract: The proprotein convertase site-1 protease (S1P) converts latent ER-membrane bound transcription factors SREBPs and ATF6 to their active forms. SREBPs are involved in cholesterol and fatty acid homeostasis whereas ATF6 is involved in unfolded protein response pathways (UPR). Cartilage-specific ablation of S1P in mice (S1Pcko) results in abnormal cartilage devoid of type II collagen protein (Col II). S1Pcko mice also lack endochondral bone development. To analyze S1Pcko cartilage we performed double-labeled immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 52 publications
(70 reference statements)
0
15
0
Order By: Relevance
“…It includes SREBP1 and 2, proteins essential for cholesterol metabolism. These factors may be critical in GPCs, as suggested by the observation that chondrocyte-specific inactivation of the gene for S1P, a proprotein convertase required to cleave SREBP precursor proteins into mature forms, results in severe chondrodysplasia in the mouse, with significant downregulation of SREBP-dependent pathways [143, 144]. …”
Section: Basic-domain Transcription Factorsmentioning
confidence: 99%
“…It includes SREBP1 and 2, proteins essential for cholesterol metabolism. These factors may be critical in GPCs, as suggested by the observation that chondrocyte-specific inactivation of the gene for S1P, a proprotein convertase required to cleave SREBP precursor proteins into mature forms, results in severe chondrodysplasia in the mouse, with significant downregulation of SREBP-dependent pathways [143, 144]. …”
Section: Basic-domain Transcription Factorsmentioning
confidence: 99%
“…The UPR is important for the normal differentiation program in chondrocytes proceeding to hypertrophy and apoptosis during growth plate development. [8890]. Inflammatory, mechanical, and oxidative stress can induce ER stress and the UPR in cartilage via C/EBP homologous protein (CHOP) and X-box protein 1 (XBP1) [••47], both of which potentiate IL-1β-induced oxidative stress and pro-catabolic responses [91]; however, XBP1 can promote chondrocyte survival under certain conditions [92].…”
Section: Autophagy Cell Survival and Bioenergeticsmentioning
confidence: 99%
“…S6) at E16.5. Our previous studies had demonstrated that S1P ablation in the chondrocyte lineage resulted in intracellular Col II entrapment with abnormal cartilage that impeded endochondral bone development (Patra et al, 2014a(Patra et al, , 2007. However, S1P-ablation in the Osx lineage results in cartilage matrix very similar to WT.…”
Section: S1p Ablation In the Osx Lineage Delays Endochondral Bone Devmentioning
confidence: 99%
“…S1P cko mice (Col2-Cre driven) suffered from a complete lack of vascular invasion where pro-Col IIB entrapment was absolute (Patra et al, 2014a(Patra et al, , 2007. This suggests that clearing of the entrapped pro-Col IIB in this zone by UPR may be necessary before vascular invasion can begin.…”
Section: S1p Ablation In the Osx Lineage Reduces The Postnatal Growthmentioning
confidence: 99%
See 1 more Smart Citation